Co-locating offshore wind and floating solar farms – Effect of high wind and wave conditions on solar power performance. (1st March 2023) - Bi, Cheng; Law, Adrian Wing-Keung
Abstract: The co-location of offshore wind and floating solar farms is an attractive hybrid option that optimizes the areal power density for the renewable power production. However, an important consideration remains whether the strong waves expected in the high-wind environment would cause large displacement of the floating solar panels and therefore significantly affect the solar power output. The present study addresses this research question by simulating the power output of a floating solar array under various high wind and wave conditions at three offshore locations, considering the effects of temperature, humidity, wind speed and wave characteristics on the system electrical behavior. The wave-platform interaction is solved with fully developed sea states to predict the fluctuating tilt angles of the solar panels. Subsequently, the total solar power output is obtained considering the solar irradiation and the estimated operating temperature. The results show that the relative changes are small in all cases, implying that the solar power output would remain stable even under high wind and wave conditions. The optimal tilt angle of the floating PV panels is also examined for the three offshore locations. The study validates the feasibility of hybrid offshore wind-solar farms, provided that structural safety has been properly considered. Highlights: Simulated power output of floating solar farms remains stable under strong winds and waves. Co-locating synergy is validated for a hybrid offshore wind and floating solar farm. Optimal initial angle for offshore PV panels ranges from 0° to 5° for the three locations considered.